Effect of operational parameters on transport and performance of a PEM fuel cell with the best protrusive gas diffusion layer arrangement. (15th June 2018) - Wu, Horng-Wen; Shih, Gin-Jang; Chen, Yi-Bin
Highlights: We numerically find best protrusive GDL arrangement to enhance cell performance. We use Taguchi method to find the optimal combined factors at the best arrangement. Stoichiometric flow ratio at cathode inlet contributes to power the most by 70%. Stoichiometric flow ratio at anode contributes most to pressure drop at anode side. Optimal combined factors upgrade cell power 12% but decrease pressure drop 35%. Abstract: The proton exchange membrane (PEM) fuel cell is regarded as the best choice in the next power generation source in recent years due to its high fuel conversion efficiency, low noise, no emissions, and so on. The performance of the PEM fuel cell is dominated by the flow field design. The authors first numerically explore how the changed flow field design by the arrangement pattern of the protrusive gas diffusion layer (GDL) affects the cell performance for a full-scale serpentine channel. The best arrangement pattern of the protrusive GDL is then used to find the optimal combined factors by Taguchi design of experiments. The optimal energy conversion and conservation for this arrangement can upgrade the PEM fuel cell performance about 12% while decreasing pressure drop is approximately 35%. In addition, employing experimental data validates the calculation results of the flow channel design. Both the numerical and the experimental results can contribute to a better comprehension of the flow phenomenon that occurs in the energy process device.